Understanding the dynamics of urban heat island as a function of development regulations - Srivastava, Vandana; Sharma, Alok; Jadon, Sanjay Singh (Journal of Environmental Engineering and Landscape Management, 2024)
This study is the first-ever attempt to relate the tools of development control like Floor Space Index (FSI/FAR), ground area covered by building footprints (BFs), and proportions/configurations of open areas, with their impact on the surface urban heat island (SUHI) which modulates the air temperatures. In the case of the Indian megacity Mumbai, statistical analysis of the land surface temperatures (LST) and its correlation with the selected development indicators, reveals that for an FSI increase of 1.0 to 1.8 the SUHI is found to be–2.5 °C less and when BFs reduced from 90% to 42% SUHI was also reduced by –2.5 °C. Highrise development with a large plot size is desirable whereas low-rise development with FSI 1.0 on small plot sizes exhibits the highest SUHI. Open spaces without vegetation do not reduce SUHI. The correlation of development regulations with SUHI intensity will help urban planners to make more informed decisions.